Laminate tailoring of composite tubular structures to improve crashworthiness design at off-axis loading - Rabiee, Ali; Ghasemnejad, Hessam (Scientific Research Publishing, 2018)
This paper presents experimental and numerical investigation on the parameters effecting energy absorption capability of composite tubular structures at oblique loading to improve crashworthiness performance. Various inclined angles of 5˚, 10˚, 20˚ and 30˚ were selected for the study of off-axis loading. The results indicate that by increasing the lateral inclination angle the mean crushing force and also energy absorption capability of all tested sections decreased. From design perspective, it is necessary to investigate the parameters effecting this phenomenon. The off-axis loading effect that causes significant reduction in energy absorption was investigated and the effected parameters were improved to increase energy absorption capability. To establish this study, 10˚ off-axis loading was chosen to illustrate the obtained improvement in energy absorption capability. Five cases were studied with combinations of ply-orientation and flat trimming with 45˚ chamfer. This method was applied to the integrated 10˚ off-axis loading and the final results showed significant improvement in energy absorption capability of composite absorbers. Finite element model (FEM) was developed to simulate the crushing process of axial and off-axis composite section in LS-DYNA and the results were in good agreement with the experimental data.
Keywords: Crashworthiness; Composites; Laminate Tailoring; Off-Axis; Oblique